L’oro blu del lago Parón. Il ruolo del capitale sociale sull’evoluzione di un conflitto socio-ambientale nel territorio della comunità Cruz de Mayo: subcuenca Lullán Parón – Huaylas – Perú - Fabio Azzolin (EtnoAntropologia)
The conflict around the water management of an important Andean lake, considerably aggraveted in 2008. The hydroelectric installations, that was grainted to Duke Energy company, was in fact occupied by the Peruvian rural community, Cruz de Mayo (CdM). This nonviolent conflict, after several years of impasse, has seen the recent introduction of various negotiating tables between CdM, Duke Energy, CEAS (a peruvian catholic association), local and state public institutions.